UNSETTLING AND UPROOTING: DEPICTION OF MIGRATION IN MOHSIN HAMID’S EXIT WEST - Raj, Arathy; Meera B (International Journal of Psychosocial Rehabilitation, 2020)
Migration, regardless of voluntary or forced has always been a representation of human individuality and group conduct. The displacement of humans from their native place is always a matter of conflict between countries. The problems and crisis that refugees face in the present world has its roots in the two World Wars. Millions of people can be seen taking shelter in different host countries. An uncertainty in economic conditions and wars are pressurising a lot of people to migrate from their own countries to other places in search of a better life. Mohsin Hamid’s Exit West (2017) is such a novel that discuss about the inescapablele relocation of people across nations and even across continents when the world is fully occupied by commotion and disorder.In world marked by this kind of hard heartedness, art often place a key role in sharing the stories of love, humanity and compassion. Exit West, shortlisted for the 2017 Booker Prize has become an epitome of such a portrayal. The novel discusses the random and frequently appearing anonymous characters in a similar imaginary world and they recount their experiences of managing in such a situation. By adding a tinge of magic realism, Hamid has created a welll-made plot that portrays the universalsal menace while at the same time it discusses about the digital influence of modern era- smart phones which is mentioned in many places in the novel. It is indeed a socially relevant novel which arrived at an apt time, a time characterised by refugee issues worldwide. Hamid asks us to visualise ourselves in the place of others as everyone share equal problems. As Hamid says, “We are all migrants through time”